1997
DOI: 10.1136/hrt.77.5.404
|View full text |Cite
|
Sign up to set email alerts
|

Acquired aortic regurgitation following occlusion of the persistent arterial duct: an echocardiographic assessment.

Abstract: Objective-To document the development of aortic regurgitation following occlusion of a patent arterial duct. Design-Case series involving nine children referred for surgical ligation of an isolated patent arterial duct. Setting-Academic referral centre. Methods-A preoperative transthoracic and transoesophageal echocardiogram was performed in theatre to look for aortic regurgitation. Thereafter, aortic flow was monitored throughout the operation by colour flow mapping with the transoesophageal probe in situ. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Harrisberg et al [7] ascribed AR following surgical PDA ligation to the dramatic rise of systemic vascular resistance resulting in an acute elevation of systemic arterial blood pressure. In addition, they suggested that retrograde diastolic blood flow in the aorta due to the increased systemic vascular capacitance proximal to the PDA contribute to AR after surgical PDA ligation [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harrisberg et al [7] ascribed AR following surgical PDA ligation to the dramatic rise of systemic vascular resistance resulting in an acute elevation of systemic arterial blood pressure. In addition, they suggested that retrograde diastolic blood flow in the aorta due to the increased systemic vascular capacitance proximal to the PDA contribute to AR after surgical PDA ligation [12].…”
Section: Discussionmentioning
confidence: 99%
“…Aortic valve regurgitation (AR) was reported after surgical ligation and coil occlusion of PDA [7,8]. However, only a small number of children were evaluated and their follow-up was short, incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies (19,22), a sudden rise of systemic arterial blood pressure by an acute elevation of systemic vascular resistance and increased vascular capacitance of proximal aorta were suggested as the mechanism of postocclusion AR. In addition, deformation of the aortic root structure by sudden hemodynamic change after PDA closure was also proposed as a cause of persistent AR (9).…”
Section: Discussionmentioning
confidence: 98%
“…However, further studies on a larger number of cases are required to evaluate this. In humans, AR is reported to be one of the possible complications following PDA occlusion (9,10,19,20). Although the exact incidence remains unknown, postocclusion AR is known to occur rarely in human patients with PDA (20).…”
Section: Discussionmentioning
confidence: 99%